2011
DOI: 10.1007/s10899-011-9282-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recessions on Gambling Expenditures

Abstract: This article examines the influence of the business cycle on expenditures of three major types of legalized gambling activities: Casino gambling, lottery, and pari-mutuel wagering. Empirical results are obtained using monthly aggregated US per capita consumption time series for the period 1959.01–2010.08. Among the three gambling activities only lottery consumption appears to be recession-proof. This series is characterized by a vast and solid growth that exceeds the growth in income and the growth in other ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 53 publications
4
23
0
Order By: Relevance
“…This result seems consistent with prior research showing that the effects of economic recession vary according to type of games (e.g. Horváth and Paap, 2012;Olason et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result seems consistent with prior research showing that the effects of economic recession vary according to type of games (e.g. Horváth and Paap, 2012;Olason et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Mao and Gu (2007) and Youn and Gu (2010) find that the casino industry is more recession-proof than the hospitality industry in general. Horváth and Paap (2012) find that only lottery consumption appears to be recessionproof, whereas casino gambling and pari-mutuel wagering expenditure were affected by the economic recession. Similarly, Cantor and Rosentraub (2012) do not find that US casinos perform better than other forms of tourism during the recession.…”
Section: Gambling Business Segments and Smes Performancementioning
confidence: 77%
“…Several point to macroeconomic factors and have demonstrated that both the money supply and interest rates influence tourist decision making about travel [8]. A few scholars have investigated the ways in which gambling activities are affected by non-macroeconomic events [9,10] but there is little understanding about how macroeconomics impact casino-visitor behavior. Only very few studies have investigated whether and how gambling activities are influenced by events.…”
Section: Introductionmentioning
confidence: 99%
“…Gambling opportunities and expenditures have increased in the United States in the past decade (Horvath & Papp 2012). Several states voted on the legalization of state lotteries, and many states expanded their lotteries to include new types of games.…”
Section: Introductionmentioning
confidence: 99%